Depth‐Sensing Macroindentation Test and Stepped Isothermal Method – Accelerated Assessment of the Local Retardation Behaviour of Thermoplastic Polymers. Issue 1 (August 2016) - Lach, Ralf; Schön, Jan; Krolopp, Tobias; Arndt, Stephan; Langer, Beate; Grellmann, Wolfgang
Summary: The prototype of a depth‐sensing macrohardness testing system with temperature chamber and temperature controlling unit for contact heating/cooling was upgraded in terms of control and software in such a way, that it allows application of the Stepped Isothermal Method (SIM) as for now. The SIM is a single‐specimen method, for which the temperature is raised stepwise at constant load and kept constant for a given time for each step, where the changes in indentation depth are measured as a function of time in this case. After correction of the thermally induced change in indentation depth and mathematical procedures a master curve construction is realised along a logarithmic time axis. The method was successfully applied to the assessment of the long‐term creep behaviour of different thermoplastic polymers such as PP, PE‐HD, PET and PVDF. The results obtained were compared with results of the SIM using tensile testing and the short‐term creep test using the depth‐sensing macrohardness testing system.